The political economy of competition law in China / Wendy Ng, University of Melbourne. - Ng, Wendy, 1980- (Cambridge University Press, 2018)
The Political Economy of Competition Law in China provides a unique perspective of China's competition law that is situated within its legal, institutional, economic, and political contexts. Adopting a framework that focuses on key stakeholders and the relevant governance and policy environment, and drawing upon stakeholder interviews, case studies, and doctrinal analysis, this book examines China's anti-monopoly law in the context of the political economy from which it emerged and in which it is now enforced. It explains the legal and economic reasoning used by Chinese competition authorities in interpreting and applying the anti-monopoly law, and offers valuable and novel insights into the processes and dynamics of law- and decision-making under that law. This book will interest scholars of competition law and professionals advising clients that operate in China, as well as scholars of Chinese law, Asian law, comparative law, and political and social science.